Synthesis and Biological Activity of Copper (Ii), Nickel(Ii) and Cobalt(Ii) With Tetradentate Schiff Bases Complexes Derived From 2-Hydroxy-1- Naphthaldehyde and Aromatic Diamines - M., Maher K.; Basheer, Huda A.; Ibrahiem., Aveen A. (Science Journal of University of Zakho, 2013)
2-hydroxy-1-napthaldehyde reacted with diaminophenol in absolute EtOH in a ratio 2:1 to give new Schiff bases (H2L1, H2L2 and H2L3). The obtained Schiff bases which were in tautomeric equilibrium (enol-imine O-H…N, keto-amine O…H-N forms)   were used as ligands to coordinate Cu (II), Ni (II), and Co (II) leading complexes. The ligands and the complexes were characterized by physicochemical, elemental and spectroscopic analyses. The complexes exhibited 1:1 metal to ligand coordination ratio ( ML1) , (ML2), (ML3). Both Ligands and complexes were evaluated for antibacterial  properties using disc diffusion method.. The complexes showed higher activity than the free ligands.
Keywords: Schiff Bases; Biological Activity; 2-Hydroxy-1-naphthaldehyde; Aromatic Diamines